Impact of cycle ergometer based low-intensity aerobic exercise on quadriceps femoris strength in breast cancer patients receiving chemotherapy - Difitasari Cipta Perdana; Indrayuni Lukitra Wardhani; Ditaruni Asrina Utami; Desak Agung Gede Suprabawati (Universitas Udayana dan Diaspora Taipei Medical University, 2025)
Background: Breast cancer and chemotherapy can reduce muscle strength through systemic and neuromusculoskeletal effects. This study aimed to evaluate the effect of low-intensity cycle ergometer exercise on quadriceps femoris strength in patients receiving chemotherapy. Methods: A randomized controlled trial was conducted at the medical rehabilitation outpatient clinic, Dr. Soetomo General Academic Hospital, Surabaya, Indonesia, from May to November 2024. Twenty female patients aged 18–59 years with stage II–III breast cancer who had completed at least three chemotherapy cycles were enrolled. Eligible participants had normal echocardiography findings (left ventricular ejection fraction ≥ 50%) and oncologist approval. Exclusion criteria included hemodynamic instability, hematologic abnormalities, arrhythmia, pulmonary disease exacerbations, recent surgery or radiotherapy, severe pain, or cognitive disorders. Participants were randomly assigned to either an intervention group or a control group. The intervention group performed low-intensity cycle ergometer training twice weekly for eight, while the control group performed breathing exercises only. Quadriceps femoris strength was measured before and after the intervention using a handheld dynamometer. Data were analyzed using paired and independent t-tests, with significance set at p-value < 0.05. Results: After eight weeks, the intervention group showed significantly greater increases in quadriceps femoris strength compared with the control group (right leg: p = 0.006; left leg: p= 0.020). Mean strength gains were 4.38 ± 2.3 kg (right) and 3.22 ± 1.9 kg (left), whereas the control group showed significant declines. Large effect sizes (Cohen’s d > 1) indicated clinically meaningful improvements in the exercise group. Conclusion: The intervention group showed significantly greater preservation and improvement of quadriceps femoris strength than the control group. Low-intensity cycle ergometer exercise appears to be a safe and effective rehabilitation strategy for maintaining muscle strength, functional capacity, and quality of life in breast cancer patients undergoing chemotherapy.